Random copolymer, crumb production method, and pneumatic tire

By using random copolymers containing aromatic Vinier, conjugated binary and ethylene structures, the problems of inconvenient treatment and high water content in the tire composition are solved, and better workingability and production efficiency are achieved.

JP7653297B2Active Publication Date: 2025-03-28ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021081160
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-16
Filing Date
2021-05-12
Publication Date
2025-03-28
Estimated Expiration
2041-05-12

AI Technical Summary

Technical Problem

In the prior art, hydrogenated polymers have problems of inconvenience in handling when used as tire compositions, and their water content is high, which affects production efficiency.

Method used

A random copolymer is adopted that contains aromatic Vinier units, conjugated binary units and ethylene structures to improve the dehydration efficiency of the particles by controlling their molecular weight distribution and particle size.

Benefits of technology

The particle size and water content of the particles are effectively controlled, and the workingability and production efficiency of the tire composition are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007653297000001
    Figure 0007653297000001
  • Figure 0007653297000002
    Figure 0007653297000002
  • Figure 0007653297000003
    Figure 0007653297000003
Patent Text Reader

Abstract

To provide a random copolymer that allows a particle size of a crumb and a moisture content to be properly controlled.SOLUTION: A random copolymer has an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an ethylene structure, has a unimodal molecular weight distribution by GPC, and has a molecular weight distribution of 1.30-1.75.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a random copolymer, a method for producing crumbs, and a pneumatic tire. [Background technology]

[0002] The widespread use of autonomous driving technology has been predicted, and this has led to a demand for reduced frequency of tire replacement, i.e., improved tire durability. In particular, with regard to braking performance, there is a demand for tires to maintain high performance for longer periods than before in order to ensure the safety of passengers. In order to improve the durability of tires, it is essential to improve the wear resistance of the tires. Conventionally, techniques have been disclosed for improving wear resistance by using polymers containing an ethylene structure in tire treads (for example, see Patent Document 1).

[0003] An example of a method for producing a polymer containing an ethylene structure is a method for producing the polymer by adding hydrogen to a conjugated diene polymer having a butadiene structural unit in the chain. For example, Patent Document 1 discloses a method for obtaining a copolymer having an ethylene structure by hydrogenating a styrene-butadiene copolymer. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 6004081 Summary of the Invention [Problem to be solved by the invention]

[0005] However, the hydrogenated polymer described in Patent Document 1 has a problem that it has poor processability when made into a tire compound. In Patent Document 1, the processability when made into a tire compound is evaluated using adhesion to a roll as an index, but in general, the evaluation of the adhesion of a polymer to a roll also correlates with the evaluation of productivity when producing the polymer. Specifically, a hydrogenated polymer with low adhesion also has low adhesion of crumbs obtained in the steam stripping step during production, and the crumbs tend to become fine. Fine crumbs tend to cause a decrease in dehydration efficiency in the dehydration step following the steam stripping step, resulting in a problem of a high water content in the finally obtained hydrogenated polymer product. Therefore, when the hydrogenated polymer described in Patent Document 1 is used as a tire compound, problems to be solved are poor processability and a high water content of the hydrogenated polymer product.

[0006] In the technology disclosed in Patent Document 1, poor processability in forming a tire compound is improved by blending two types of polymers, a high molecular weight hydrogenated polymer and a low molecular weight hydrogenated polymer, but since the high molecular weight hydrogenated polymer and the low molecular weight hydrogenated polymer are produced separately, the problem of the high molecular weight hydrogenated polymer having an excessively high water content remains unresolved. Therefore, in order to improve the productivity in producing hydrogenated polymers, a technology is desired that can appropriately control the particle size of the crumbs obtained in the steam stripping step and appropriately control the water content of the hydrogenated polymer.

[0007] In view of the above-mentioned problems in the prior art, an object of the present invention is to provide a random copolymer which can appropriately control the particle size and water content of crumbs and has excellent productivity. [Means for solving the problem]

[0008] As a result of intensive research into solving the problems of the conventional techniques described above, the present inventors discovered that a random copolymer having a specific structure can solve the problems of the conventional techniques described above, and thus completed the present invention. That is, the present invention is as follows.

[0009] 〔1〕 La 1. A method for producing a crumb of a random copolymer, comprising: Aromatic vinyl compounds and conjugated diene compounds Monomers containing , polymerization in solution Thus, a random copolymer having an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an ethylene structure, and having a monomodal molecular weight distribution measured by GPC of 1.30 to 1.75 is obtained. The process and The random Obtaining crumbs by removing the solvent from a solution containing a polymer; , Obtain crumbs with a median diameter (D50) of 6.0 mm or more and 12.0 mm or less. Method for producing crumbs. Effect of the Invention

[0010] According to the present invention, a random copolymerization can be provided that allows the particle size and moisture content of the crumbs to be appropriately controlled. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. It should be noted that the following embodiment is merely an example for explaining the present invention, and the present invention is not limited to the following embodiment. The present invention can be practiced with appropriate modifications within the scope of the gist of the present invention.

[0012] [Random Copolymer] The random copolymer of the present embodiment is It has an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an ethylene structure, and the molecular weight distribution measured by GPC (gel permeation chromatography) is monomodal and is 1.30 to 1.75. By specifying the random copolymer of this embodiment to have the above-mentioned configuration, particularly the molecular weight distribution within the above-mentioned range, when a random copolymer having a weight average molecular weight suitable for use in a tire composition is obtained, the crumb particle size does not become too fine, thereby achieving excellent crumb dewatering efficiency. By setting the molecular weight distribution within the above specific range, the proportion of low molecular weight components that are effective in enlarging the crumb particle size can be increased, so that the crumbs can be enlarged appropriately and the crumb particle size can be prevented from becoming excessively fine.

[0013] (GPC curve shape of random copolymer) The GPC curve of the random copolymer of this embodiment is unimodal. A unimodal GPC curve means that the slope of the tangent to the elution curve when elution time is changed is 0° only once. When batch polymerization is performed and a coupling reaction is performed, the coupling product and the polymer before coupling will show multiple peaks and will not be monomodal unless the modification rate is 100%. On the other hand, a polymer produced by continuous polymerization will have only one peak in the GPC curve. When a coupling reaction is performed, a shoulder may be formed on the low molecular weight side, but multiple peaks will not be formed. Therefore, a polymer produced by continuous polymerization can have a monomodal GPC curve of a random copolymer unless polymers of different molecular weight ranges are blended. The molecular weight distribution of the random copolymer can be controlled by adjusting the ratio of the inner height (L) to the diameter (D) of the polymerization reactor.

[0014] (Structure of random copolymer) The random copolymer of the present embodiment has an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an ethylene structure. Here, the "ethylene structure" refers to a structure in which ethylene monomers are repeating units, and carbon atoms are linked together via single bonds. The "ethylene structure" is not limited to the case where it is formed by polymerizing an ethylene monomer, but also includes the case where the ethylene structure is formed by adding hydrogen to a conjugated diene portion, as described later. The random copolymer of the present embodiment is preferably a hydrogenated copolymer in which an ethylene structure is formed by adding hydrogen to a copolymer having an aromatic portion, which is an aromatic vinyl monomer unit, and a conjugated diene portion, which is a conjugated diene monomer unit, from the viewpoint of commercial production. However, it may also be a random copolymer in which an aromatic vinyl compound, a conjugated diene compound, and ethylene are copolymerized. A hydrogenated copolymer is a copolymer in which hydrogen is added to the double bond moieties in the conjugated diene moieties, and part or all of the conjugated diene moieties are converted to ethylene structures. By increasing the hydrogenation rate, the content of ethylene structures can be increased.

[0015] In addition, when the random copolymer of the present embodiment is a hydrogenated copolymer, the ethylene structure is defined as a structure in which hydrogen has been added to the polymer chain at both ends of the main chain of the conjugated diene compound (for example, 1,4-bonds in a polymer in which 1,3-butadiene is used as a monomer), and the ethylene structure does not include structures in which hydrogen has been added to other forms (for example, 1,2-bonds (vinyl bonds) in a polymer in which 1,3-butadiene is used as a monomer). The ethylene structure is 1 It can be calculated from the spectral reduction rate of the unsaturated bond derived from the 1,4-bond of the conjugated diene compound in the spectrum obtained by measuring H-NMR.

[0016] Examples of aromatic vinyl compounds used to form aromatic vinyl monomer units include, but are not limited to, styrene, 4-methylstyrene, α-methylstyrene, 1-vinylnaphthalene, 3-vinyltoluene, ethylvinylbenzene, divinylbenzene, 4-cyclohexylstyrene, and 2,4,6-trimethylstyrene. These may be used alone or in combination of two or more. Among these, styrene is particularly preferred from the viewpoint of practical aspects such as easy availability of monomers.

[0017] Conjugated diene compounds used to form conjugated diene monomer units include, but are not limited to, 1,3-butadiene, isoprene, 1,3-pentadiene, 2,3-dimethylbutadiene, 2-phenyl-1,3-butadiene, 1,3-hexadiene, etc. These may be used alone or in combination of two or more. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred, from the viewpoint of practical aspects such as easy availability of monomers.

[0018] In the random copolymer of the present embodiment, when the content of chains each consisting of 8 or more consecutive aromatic vinyl monomer units is defined as the long chain ratio, the long chain ratio is preferably 10 mass% or less based on the total aromatic vinyl monomer units. When the proportion of long chains is 10% by mass or less, excellent fuel economy tends to be obtained. The content of long chains consisting of eight or more consecutive aromatic vinyl monomer units (long chain ratio) was measured using a random copolymer in deuterated chloroform as a solvent. 1 It can be obtained by calculating the ratio of the integral value in the range (a) to the total integral values ​​in each of the chemical shift ranges (a) to (c) in the H-NMR spectrum. For example, if the aromatic vinyl is styrene, the proportion of styrene can be calculated by finding the ratio of the integral value in range (a) to the sum of the integral values ​​in ranges (a) to (c) and multiplying this value by 2.5. This allows the chain state of the aromatic vinyl monomer units to be understood. (a) Aromatic vinyl compounds with 8 or more chains: 6.00≦S<6.68 (b) Aromatic vinyl compound chains 2-7: 6.68≦S<6.89 (c) Aromatic vinyl compound short chain: 6.89≦S≦8.00

[0019] Furthermore, the random copolymer of the present embodiment may be modified or unmodified, but is preferably a hydrogenated modified random copolymer from the viewpoints of braking performance and wear resistance. The above-mentioned modification means that the random copolymer is functionalized with a compound having a nitrogen element. The type of modification may be either chain end modification, which modifies the polymer chain end, or main chain modification, which copolymerizes a compound having a nitrogen element during polymerization.

[0020] (Iodine value of random copolymer) From the viewpoint of crosslinkability, the random copolymer preferably has an iodine value of 14 or more, more preferably 30 or more, even more preferably 70 or more, and even more preferably 100 or more. From the viewpoint of crosslink density, it is preferably 200 or less, more preferably 180 or less, and further preferably 160 or less. The iodine value can be measured by the method described in the Examples below. The iodine value of the random copolymer of the present embodiment can be controlled within the above range by adjusting the mass ratio of the conjugated diene compound to the aromatic vinyl monomer in the random copolymer and the hydrogen conversion rate. Specifically, when the mass ratio of the aromatic vinyl monomer in the random copolymer is 30 mass %, the iodine value can be controlled to 100 or more by setting the hydrogen conversion rate to 69% or less. Furthermore, when the hydrogen conversion rate is set to 70%, the iodine value can be controlled to 100 or more by setting the proportion of aromatic vinyl monomer in the random copolymer to 29 mass % or less.

[0021] (Hydrogenation rate of random copolymer) The hydrogenation rate of the random copolymer of the present embodiment (the ratio of hydrogenation to the conjugated diene portion) is preferably 50 mol% or more, more preferably 60 mol% or more, and even more preferably 70 mol% or more from the viewpoint of crosslinkability. Also, from the viewpoint of crosslinkability, it is preferably 95 mol% or less, more preferably 90 mol% or less, and even more preferably 85 mol% or less. The hydrogenation rate is 1 It can be calculated from the spectral reduction rate of the unsaturated bond part of the spectrum obtained by measuring H-NMR.

[0022] (Content of aromatic vinyl monomer units in random copolymer) In 100% by mass of the random copolymer of this embodiment, the content of aromatic vinyl monomer units is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more from the viewpoint of wet grip performance when processed into a tire, and is preferably 60% by mass or less, more preferably 50% by mass or less from the viewpoint of fuel efficiency. The content of the aromatic vinyl monomer unit can be measured by the method described in the Examples below.

[0023] (Weight average molecular weight of random copolymer) The weight average molecular weight (Mw) of the random copolymer of the present embodiment is preferably 300,000 or more and 800,000 or less. From the viewpoint of abrasion resistance when the random copolymer of the present embodiment is used in a tire composition, the molecular weight is preferably 300,000 or more, more preferably 400,000 or more, and even more preferably 450,000 or more, and from the viewpoint of Mooney viscosity, the molecular weight is preferably 800,000 or less, more preferably 700,000 or less, even more preferably 600,000 or less, and even more preferably 550,000 or less. The weight average molecular weight of the random copolymer can be controlled within the above numerical range by adjusting the polymerization conditions, such as the amount of monomer added in the polymerization step, the polymerization time, and the polymerization temperature.

[0024] (Molecular weight distribution of random copolymer) The molecular weight distribution (Mw / Mn) of the random copolymer of this embodiment is 1.30 or more and 1.75 or less. The molecular weight distribution of the random copolymer affects the size of crumbs formed during steam stripping of a polymerization solution of the random copolymer. When the molecular weight distribution is narrow, the proportion of sticky low molecular weight components is small, resulting in fine crumbs, and insufficient shear pressure is applied in the dehydration process using an extruder following the steam stripping process, resulting in reduced dehydration efficiency. When the molecular weight distribution is too wide, the proportion of sticky low molecular weight components is high, resulting in excessively large crumbs. If the crumbs are too large, the drying efficiency in the hot box deteriorates, resulting in reduced crumb drying efficiency. If we focus only on sticky low molecular weight components, the amount of low molecular weight components will be large even when the average molecular weight is small, but in that case, although the crumbs will be large, the dehydration efficiency tends to decrease. Therefore, from the perspective of improving production efficiency, it is more appropriate to control the molecular weight distribution rather than reducing the overall molecular weight. From the above, the molecular weight distribution of the random copolymer of this embodiment is 1.30 or more, preferably 1.40 or more, and more preferably 1.50 or more, from the viewpoint of increasing the average particle size of the crumbs generated during steam stripping. In order to prevent the average particle size of the crumbs from becoming too large, the molecular weight distribution of the random copolymer of this embodiment is 1.75 or less, preferably 1.70 or less, and more preferably 1.65 or less.

[0025] In a continuous polymerization process, the molecular weight distribution of a random copolymer can be controlled by adjusting the aspect ratio (L / D) of a polymerization reactor and by adjusting the polymerization temperature. In order to control the molecular weight distribution to 1.75 or less, the L / D ratio of the polymerization reactor is preferably 4.0 or more, more preferably 6.0 or more, and further preferably 7.0 or more. Similarly, from the viewpoint of controlling the molecular weight distribution to 1.75 or less, the temperature of the polymerization reactor is preferably 80° C. or less, more preferably 75° C. or less, and further preferably 72° C. or less. On the other hand, from the viewpoint of controlling the molecular weight distribution to 1.3 or more, in the continuous polymerization process, L / D is preferably 1.0 or more, more preferably 2.0 or more, and even more preferably 3.0 or more. In order to control the molecular weight distribution, it is preferable to select a monomer that undergoes quantitative polymerization and is unlikely to cause side reactions. From the viewpoint of quantitatively proceeding anionic polymerization, which is unlikely to cause side reactions, and controlling the molecular weight distribution, the conjugated diene compound is preferably 1,3-butadiene or isoprene. Similarly, from the viewpoint of controlling the molecular weight distribution, the aromatic vinyl compound is preferably styrene or 4-methylstyrene. The weight average molecular weight (Mw) and number average molecular weight (Mn) are measured by the method described in the Examples below.

[0026] (Glass transition temperature of random copolymer) The glass transition temperature (Tg) of the random copolymer of the present embodiment is preferably −70° C. or higher, more preferably −50° C. or higher, even more preferably −40° C. or higher, and even more preferably −30° C. or higher, from the viewpoint of braking performance. Also, from the viewpoint of low-temperature properties of the tire, it is preferably −10° C. or lower, more preferably −15° C. or lower, even more preferably −20° C. or lower, and even more preferably −50° C. or lower. The Tg of the random copolymer can be controlled by adjusting the composition ratio of the aromatic vinyl monomer unit and the conjugated diene monomer unit, and the iodine value. Specifically, the Tg of the random copolymer can be increased by increasing the composition ratio of the aromatic vinyl monomer unit, and the Tg of the random copolymer can be increased by increasing the amount of 1,2-bonds in the conjugated diene monomer unit. More specifically, when the content of the aromatic vinyl monomer unit in the random copolymer is 20% by mass, the Tg can be made -50°C or higher by setting the iodine value to about 38 to 94. On the other hand, when the iodine value is set to 110, the Tg can be made -50°C or higher by setting the content of the aromatic vinyl monomer unit to 20% by mass or higher. The glass transition temperature (Tg) can be measured by the method described in the Examples below.

[0027] [Method for producing random copolymer] The random copolymer of the present embodiment can be produced through a polymerization step, a modification step, and a hydrogenation step.

[0028] (Polymerization process) There is no particular limitation on the polymerization method for the random copolymer, and any of solution polymerization, gas phase polymerization and bulk polymerization methods can be used, but from the viewpoint of commercial production, solution polymerization is particularly preferred. In this embodiment, the polymerization method is preferably a continuous method. When a solution polymerization method is used, the monomer concentration in the solution is preferably 5% by mass or more, more preferably 10% by mass or more. When the monomer concentration in the solution is 5% by mass or more, the amount of the obtained random copolymer is sufficient, which is preferable from the viewpoint of cost. In addition, the monomer concentration in the solution is preferably 50% by mass or less, more preferably 30% by mass or less. When the monomer concentration in the solution is 50% by mass or less, the solution viscosity can be prevented from becoming too high, stirring is easily performed, and the polymerization process tends to be easily carried out.

[0029] <Polymerization initiator> When anionic polymerization is carried out in the polymerization step, the polymerization initiator is not particularly limited, but an organolithium compound is preferably used. The organic lithium compound is preferably one having an alkyl group having 2 to 20 carbon atoms, such as ethyl lithium, n-propyl lithium, isopropyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, tert-octyl lithium, n-decyl lithium, phenyl lithium, 2-naphthyl lithium, 2-butyl-phenyl lithium, 4-phenyl-butyl lithium, cyclohexyl lithium, cyclopentyl lithium, a reaction product of diisopropenylbenzene and butyl lithium, etc. Among these, n-butyl lithium and sec-butyl lithium are preferred from the viewpoints of availability, safety, etc. When coordination polymerization is performed in the polymerization step, it is preferable to use, for example, the polymerization catalyst composition described in JP-A-2020-45500 as the polymerization initiator.

[0030] <Polymerization method> The method for producing a random copolymer by anionic polymerization or coordination polymerization using a polymerization initiator is not particularly limited, and any conventionally known method can be used. Specifically, in an organic solvent inert to the reaction, for example, a hydrocarbon solvent such as an aliphatic, alicyclic, or aromatic hydrocarbon compound, styrene, 1,3-butadiene, ethylene, or the like is polymerized using, for example, butyllithium as a polymerization initiator, and, if necessary, in the presence of a randomizer described below, to obtain the desired random copolymer.

[0031] <Hydrocarbon solvents> The hydrocarbon solvent is preferably one having 3 to 8 carbon atoms, and examples thereof include, but are not limited to, propane, n-butane, isobutane, n-pentane, isopentane, n-hexane, cyclohexane, propene, 1-butene, isobutene, trans-2-butene, cis-2-butene, 1-pentene, 2-pentene, 1-hexene, 2-hexene, benzene, toluene, xylene, and ethylbenzene. These may be used alone or in combination of two or more.

[0032] <Randomizer in anionic polymerization> The randomizer is a compound having an effect of controlling the microstructure of the conjugated diene portion in a copolymer, for example, increasing the number of 1,2-bonds in butadiene and 3,4-bonds in isoprene, or of controlling the composition distribution of monomer units in a copolymer, for example, randomizing the styrene units and butadiene units in a styrene-butadiene copolymer. The randomizer is not particularly limited, and any of the known compounds that have been generally used as a conventional randomizer can be used. Examples of the randomizer include, but are not limited to, ethers and tertiary amines such as dimethoxybenzene, tetrahydrofuran, dimethoxyethane, diethylene glycol dibutyl ether, diethylene glycol dimethyl ether, 2,2-di(2-tetrahydrofuryl)propane, triethylamine, pyridine, N-methylmorpholine, N,N,N',N'-tetramethylethylenediamine, and 1,2-dipiperidinoethane. Potassium salts such as potassium t-amylate and potassium t-butoxide, and sodium salts such as sodium t-amylate can also be used. These randomizers may be used alone or in combination of two or more. The amount of the randomizer used is preferably 0.01 molar equivalents or more, more preferably 0.05 molar equivalents or more, per mole of the organolithium compound as the polymerization initiator. By making the amount of the randomizer used 0.01 molar equivalents or more, the effect of addition is obtained, and the randomization tends to be easy. The amount of the randomizer used is preferably 1000 molar equivalents or less, more preferably 500 molar equivalents or less, per mole of the organolithium compound. By making the amount of the randomizer used 1000 molar equivalents or less, the reaction rate of the monomer can be prevented from changing significantly, and the randomization tends to be easy.

[0033] <Reaction temperature> The reaction temperature during polymerization is not particularly limited as long as the reaction proceeds favorably, but is preferably from -10°C to 100°C, more preferably from 25°C to 70°C.

[0034] (Denaturation process) By reacting the active terminal of the random copolymer obtained by the polymerization step with a compound having a functional group that interacts with silica, a functional group that interacts with silica can be introduced into the polymerization end terminal of the random copolymer, thereby obtaining a random copolymer with a modified polymerization end terminal. The random copolymer used in the modification reaction (hereinafter also referred to as terminal modification reaction) may be one whose polymerization initiation terminal is unmodified or modified, so long as it has an active terminal. The compound used in the modification step is not particularly limited as long as it has a functional group that interacts with silica and can react with the polymerization active terminal. For example, it is preferable to use a terminal modifying agent containing a tin atom or a nitrogen atom, and it is more preferable to use a terminal modifying agent containing a nitrogen atom.

[0035] The modification process also includes a coupling process accompanied by an increase in molecular weight. Specifically, a random copolymer having a branched structure can be obtained by reacting the active terminal with a coupling agent having multiple reactive sites. The nitrogen-containing coupling agent is called a modifier, and by selecting a compound having a coupling function as the modifier, a coupling effect can be obtained by the modification step. In a modification reaction accompanied by an increase in molecular weight, the modification rate (coupling rate) affects the molecular weight distribution. Therefore, from the viewpoint of controlling the molecular weight distribution to 1.75 or less, the modification rate is preferably 60% or more, more preferably 70% or more, and even more preferably 75% or more. When a modifying agent having multiple functional groups is used, a hyperbranched polymer is produced by coupling. Regardless of the number of functional groups, if the modification rate is high, the molecular weight distribution tends to shift while maintaining its sharpness. Since the structure of the modifier has little effect on the molecular weight distribution, it can be selected depending on the functions expected of the random copolymer to be produced. The modification rate can be measured by the method described in the Examples below.

[0036] As the nitrogen atom-containing terminal modifying agent, from the viewpoints of polymerization productivity and a high modification rate, preferred examples thereof include isocyanate compounds, isothiocyanate compounds, isocyanuric acid derivatives, nitrogen group-containing carbonyl compounds, nitrogen group-containing vinyl compounds, nitrogen group-containing epoxy compounds, and nitrogen group-containing alkoxysilane compounds. As these nitrogen atom-containing terminal modifiers, nitrogen group-containing alkoxysilane compounds are more preferred from the viewpoints of polymerization productivity, high modification rate, and tensile strength when made into a tire.

[0037] Examples of the nitrogen group-containing alkoxysilane compound include, but are not limited to, 2,2-dimethoxy-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane, 2,2-dimethoxy-1-(4-trimethoxysilylbutyl)-1-aza-2-silacyclohexane, 2,2-dimethoxy-1-(5-trimethoxysilylpentyl)-1-aza-2-silacyclohexane, and the like. )-1-aza-2-silacycloheptane, 2,2-dimethoxy-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, 2,2-diethoxy-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, 2-methoxy,2-methyl-1-(3-trimethoxysilylpropyl)-1-aza-2-silacyclopentane, 2-ethoxy,2-ethyl-1-(3-triethoxysilylpropyl)-1-aza-2-silacyclopentane Clopentane, 2-methoxy, 2-methyl-1-(3-dimethoxymethylsilylpropyl)-1-aza-2-silacyclopentane, and 2-ethoxy, 2-ethyl-1-(3-diethoxyethylsilylpropyl)-1-aza-2-silacyclopentane, tris(3-trimethoxysilylpropyl)amine, tris(3-methyldimethoxysilylpropyl)amine, tris(3-triethoxysilylpropyl)amine, tris(3-methyldiethoxysilylpropyl)amine Amines, tris(trimethoxysilylmethyl)amine, tris(2-trimethoxysilylethyl)amine, and tris(4-trimethoxysilylbutyl)amine, tetrakis[3-(2,2-dimethoxy-1-aza-2-silacyclopentane)propyl]-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-propanediamine, tetrakis(3-trimethoxysilylpropyl)-1,3-bisaminomethylcyclohexane, and N 1-(3-(bis(3-(trimethoxysilyl)propyl)amino)propyl)-N 1 -Methyl-N 3 -(3-(methyl(3-(trimethoxysilyl)propyl)amino)propyl)-N 3 -(3-(trimethoxysilyl)propyl)-1,3-propanediamine.

[0038] The terminal modification reaction can be carried out, for example, as a solution reaction. This solution reaction may be carried out using a solution containing unreacted monomers after the polymerization reaction in the polymerization step, or may be carried out after isolating the copolymer contained in the solution and dissolving it in a suitable solvent such as cyclohexane. In addition, since the polymerization method is continuous, the terminal modification reaction is also preferably continuous. In this case, the method of adding the terminal modifying agent is not particularly limited, and examples thereof include a method of adding the agent all at once, a method of adding the agent in portions, and a method of adding the agent continuously. The amount of the compound used in the terminal modification reaction may be appropriately set according to the type of compound used in the reaction, but is preferably 0.1 molar equivalent or more, more preferably 0.3 molar equivalent or more, relative to the metal atom involved in the polymerization reaction of the polymerization initiator. By setting the amount to 0.1 molar equivalent or more, the modification reaction can be sufficiently progressed, and the dispersibility of silica can be suitably improved. The temperature of the terminal modification reaction is usually the same as the temperature of the polymerization reaction, and is preferably −20 to 150° C., more preferably 0 to 120° C., and further preferably 20 to 100° C. If the temperature of the modification reaction is low, the viscosity of the modified copolymer tends to increase. On the other hand, if the temperature of the modification reaction is high, the polymerization active terminals are likely to be deactivated. The reaction time of the modification reaction is preferably 1 minute to 5 hours, and more preferably 2 minutes to 1 hour.

[0039] (Reaction termination step) The anionic polymerization can be terminated by adding a known reaction terminator, which includes, but is not limited to, alcohols such as methanol, ethanol, and isopropanol, polar solvents having active protons such as acetic acid, and mixtures thereof, or mixtures of such polar solvents with non-polar solvents such as hexane and cyclohexane. The amount of the reaction terminator added is usually sufficient if it is about the same molar amount or about twice the molar amount of the anionic polymerization initiator.

[0040] (Hydrogenation process) When the random copolymer of the present embodiment is converted into a hydrogenated copolymer, the hydrogenation method and reaction conditions are not particularly limited, and hydrogenation may be performed by a known method under known conditions. The reaction is usually carried out at 20 to 150° C. under a hydrogen pressure of 0.1 to 10 MPa in the presence of a hydrogenation catalyst. The hydrogenation rate can be controlled by adjusting the amount of hydrogenation catalyst, the hydrogen pressure during the hydrogenation reaction, the reaction time, etc. As the hydrogenation catalyst, a compound containing any of metals in Groups 4 to 11 of the Periodic Table can usually be used. For example, compounds containing Ti, V, Co, Ni, Zr, Ru, Rh, Pd, Hf, Re, and Pt atoms can be used as the hydrogenation catalyst, but are not limited to the following. More specifically, metallocene compounds such as Ti, Zr, Hf, Co, Ni, Pd, Pt, Ru, Rh, and Re; supported heterogeneous catalysts in which metals such as Pd, Ni, Pt, Rh, and Ru are supported on a support such as carbon, silica, alumina, and diatomaceous earth; homogeneous Ziegler-type catalysts in which an organic salt or acetylacetone salt of a metal element such as Ni or Co is combined with a reducing agent such as organoaluminum; organometallic compounds or complexes such as Ru and Rh; and fullerenes and carbon nanotubes in which hydrogen is absorbed. Among these, metallocene compounds containing any one of Ti, Zr, Hf, Co and Ni are preferred from the viewpoint of being capable of undergoing a hydrogenation reaction in a homogeneous system in an inert organic solvent, and metallocene compounds containing any one of Ti, Zr and Hf are more preferred. The hydrogenation catalyst may be used alone or in combination of two or more kinds.

[0041] A preferred method for producing the random copolymer of the present embodiment is to carry out solution polymerization, and then subject the resulting polymer solution as is to a modification treatment as necessary, and then to a hydrogenation step as necessary. The random copolymer of the present embodiment is obtained by removing the solvent from the polymer solution obtained above and isolating the polymer. Examples of the method for isolating the random copolymer include a known method for removing the solvent such as steam stripping, and a method for isolating the polymer by a drying operation such as heat treatment using a dehydrating extruder, a drying extruder, or a conveyer.

[0042] (Crumb manufacturing method) The random copolymer of the present embodiment can be isolated as crumbs by removing the solvent from the polymerization solution. Specifically, the solvent is removed in a steam stripping process to obtain crumbs. The particle size of the resulting crumbs affects the drying capacity in the dehydration extrusion process, the drying extrusion process, and the conveyor process that follow the desolvation process. If the average particle size of the crumbs is too large, the dehydration efficiency in the drying conveyor decreases, and the moisture content in the product bale increases. On the other hand, if the average particle size of the crumbs is too small, sufficient shear pressure is not applied in the dehydration extruder or drying extruder, resulting in a decrease in dehydration efficiency and an increase in the moisture content in the product bale. In order to prevent the particle size of the crumbs from becoming too large, the temperature of the steam stripping is preferably 70°C or higher, more preferably 80°C or higher, and even more preferably 90°C or higher. From the viewpoint of the amount of steam used, the temperature of the steam stripping is preferably 110° C. or lower, more preferably 100° C. or lower, and even more preferably 95° C. or lower.

[0043] <Crumb particle size> The average particle size of the crumbs is preferably determined by the particle size distribution of the crumbs. In particular, the median diameter (D50), which is the median value of the particle size of the crumbs, is an important value for the drying process. The particle size of crumbs varies, and the ratio of large to small crumbs greatly affects the dehydration efficiency of the entire crumbs. Therefore, the median value, D50, is an index of the drying efficiency of the entire crumbs. As described above, the D50 of the crumb can be controlled by adjusting the molecular weight distribution of the random copolymer to 1.30 to 1.75. From the viewpoint of the dehydration efficiency in the crumb dehydration extruder, the median diameter (D50) of the crumb of the random copolymer of this embodiment is preferably 6.0 mm or more, more preferably 8.0 mm or more, even more preferably 8.5 mm or more, and even more preferably 9.0 mm or more. From the viewpoint of dehydration efficiency on the crumb drying conveyor, the D50 of the crumb of the random copolymer of this embodiment is preferably 12.0 mm or less, more preferably 11 mm or less, and further preferably 10 mm or less. The D50 of the crumb can be measured by the method described in the Examples below.

[0044] [Rubber composition] A rubber composition can be obtained by combining the random copolymer of the present embodiment with other rubber components than the random copolymer, a plasticizer component, a filler component, and other additives as necessary. <Other rubber components> The rubber composition may contain a known polymer blend as a rubber component other than the random copolymer of the present embodiment. In addition to the above-mentioned polymer blend, a rubber commonly used in general tire rubber compositions can be used, such as natural rubber (NR), isoprene rubber (IR), styrene butadiene rubber (SBR), butadiene rubber (BR), etc. These may be used alone or in combination of two or more. The rubber composition is not particularly limited in terms of the content of the filler component (A) and the content of the plasticizer component (B). Taking the entire rubber composition as 100% by mass, the content of the filler component is preferably 20 to 50% by mass, and the content of the plasticizer component is preferably 10 to 40% by mass.

[0045] <Filler component> The filler component is compounded in the rubber composition for the purpose of reinforcing the rubber, and includes, but is not limited to, white fillers (inorganic fillers) such as silica, calcium carbonate, mica, aluminum hydroxide, magnesium oxide, magnesium hydroxide, clay, talc, alumina, titanium oxide, and mica, and carbon black. These may be used alone or in combination of two or more. In particular, silica and carbon black are preferred, and a combination of these is more preferred.

[0046] The silica is not particularly limited, and examples thereof include dry process silica (anhydrous silica) and wet process silica (hydrated silica), with wet process silica being preferred because it contains many silanol groups. From the viewpoint of wear resistance, the nitrogen adsorption specific surface area (N2SA) of silica is preferably 60 m 2 / g or more, more preferably 120m 2 / g or more, and from the viewpoint of fuel economy, it is preferably 300m 2 / g or less, more preferably 200m 2 / g or less. The nitrogen adsorption specific surface area of ​​silica is a value measured by the BET method in accordance with ASTM D3037-81. From the viewpoint of fuel economy, the content of silica is preferably 30 parts by mass or more, and more preferably 50 parts by mass or more, per 100 parts by mass of the rubber component containing the random copolymer of this embodiment and other rubber components, and from the viewpoint of Mooney viscosity, the content of silica is preferably 120 parts by mass or less, and more preferably 100 parts by mass or less.

[0047] Examples of carbon black include furnace blacks (furnace carbon blacks) such as SAF, ISAF, HAF, MAF, FEF, SRF, GPF, APF, FF, CF, SCF, and ECF; acetylene blacks (acetylene carbon blacks); thermal blacks (thermal carbon blacks) such as FT and MT; channel blacks (channel carbon blacks) such as EPC, MPC, and CC; and graphite. These may be used alone or in combination of two or more. The nitrogen adsorption specific surface area (N2SA) of carbon black is usually 5 to 200 m 2 / g, and from the viewpoint of abrasion resistance, preferably 50m 2 / g or more, more preferably 80m 2 / g or more, and from the viewpoint of fuel economy, it is preferably 150 m 2 / g or less, more preferably 120m 2 / g or less. The dibutyl phthalate (DBP) absorption amount of carbon black is usually 5 to 300 mL / 100 g, and it is preferable that the lower limit is 80 mL / 100 g and the upper limit is 180 mL / 100 g. The nitrogen adsorption specific surface area can be measured according to ASTM D4820-93, and the DBP absorption can be measured according to ASTM D2414-93. From the viewpoint of abrasion resistance, the amount of carbon black is preferably 1 part by mass or more, and more preferably 3 parts by mass or more, per 100 parts by mass of the rubber component containing the random copolymer of this embodiment and other rubber components. From the viewpoint of fuel economy, the amount of carbon black is preferably 30 parts by mass or less, and more preferably 15 parts by mass or less, per 100 parts by mass of the rubber component.

[0048] Silica is preferably used in combination with a silane coupling agent. As the silane coupling agent, a conventionally known agent can be used. Examples of the sulfide-based compounds include, but are not limited to, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-triethoxysilylethyl)tetrasulfide, bis(3-trimethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(3-triethoxysilylpropyl)trisulfide, bis(3-trimethoxysilylpropyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, bis(3-trimethoxysilylpropyl)disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyltetrasulfide, 3-trimethoxysilylpropylbenzothiazolyltetrasulfide, 3-triethoxysilylpropylbenzothiazoletetrasulfide, 3-triethoxysilylpropylmethacrylatemonosulfide, and 3-trimethoxysilylpropylmethacrylatemonosulfide. Examples of the sulfide-based compounds include, but are not limited to, bis(3-triethoxysilylpropyl)tetrasulfide, bis(2-trimethoxysilylethyl)tetrasulfide, bis(3-triethoxysilylpropyl)trisulfide, bis(3-triethoxysilylpropyl)disulfide, 3-trimethoxysilylpropyl-N,N-dimethylthiocarbamoyltetrasulfide, 3-trimethoxysilylpropylbenzothiazolyltetrasulfide, 3-triethoxysilylpropylbenzothiazoletetrasulfide, 3-triethoxysilylpropylmethacrylatemonosulfide, and 3-trimethoxysilylpropylmethacrylatemonosulfide. mercapto-based silanes such as mercaptopropyltriethoxysilane, 2-mercaptoethyltrimethoxysilane, and 2-mercaptoethyltriethoxysilane; vinyl-based silanes such as vinyltriethoxysilane and vinyltrimethoxysilane; amino-based silanes such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, 3-(2-aminoethyl)aminopropyltriethoxysilane, and 3-(2-aminoethyl)aminopropyltrimethoxysilane; glycidoxy-based silanes such as γ-glycidoxypropyltriethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxypropylmethyldiethoxysilane, and γ-glycidoxypropylmethyldimethoxysilane; nitro-based silanes such as 3-nitropropyltrimethoxysilane and 3-nitropropyltriethoxysilane; and chloro-based silanes such as 3-chloropropyltrimethoxysilane, 3-chloropropyltriethoxysilane, 2-chloroethyltrimethoxysilane, and 2-chloroethyltriethoxysilane. The silane coupling agent may be used alone or in combination of two or more. In particular, from the viewpoints of the coupling effect, processability, and cost of the silane coupling agent, sulfide-based silane coupling agents are preferred, and bis(3-triethoxysilylpropyl)tetrasulfide and bis(3-triethoxysilylpropyl)disulfide are more preferred. The content of the silane coupling agent is preferably 3 parts by mass or more, and more preferably 5 parts by mass or more, per 100 parts by mass of silica from the viewpoints of fuel economy and abrasion resistance, and is preferably 15 parts by mass or less, and more preferably 10 parts by mass or less, per 100 parts by mass of silica from the viewpoint of Mooney viscosity.

[0049] <Plasticizer component> Examples of the plasticizer component include, but are not limited to, oil, resin, antioxidant, wax, stearic acid, vulcanization accelerator, etc. These may be used alone or in combination of two or more. Examples of the oil include aromatic mineral oils (viscosity specific gravity constant (VGC value) 0.900 to 1.049), naphthenic mineral oils (VGC value 0.850 to 0.899), and paraffinic mineral oils (VGC value 0.790 to 0.849). The polycyclic aromatic content of the extender oil is preferably less than 3 mass%, more preferably less than 1 mass%. The polycyclic aromatic content is measured according to the British Petroleum Institute 346 / 92 method. The aromatic compound content (CA) of the extender oil is preferably 20 mass% or more. Two or more of these extender oils may be used in combination. From the viewpoint of Mooney viscosity of the rubber composition, the oil content is preferably 5 parts by mass or more, and more preferably 10 parts by mass or more, per 100 parts by mass of the rubber component containing the random copolymer of this embodiment and other rubber components. Also, from the viewpoint of fuel economy, the oil content is preferably 50 parts by mass or less, and more preferably 40 parts by mass or less, per 100 parts by mass of the rubber component containing the random copolymer of this embodiment and other rubber components. Examples of resins include, but are not limited to, C5 petroleum resins, C9 petroleum resins, coumarone-indene resins, indene resins, phenolic resins, and copolymers of α-methylstyrene and / or styrene. These may be used alone or in combination of two or more. In particular, coumarone-indene resin, phenolic resin (particularly, terpene phenolic resin), and copolymer of α-methylstyrene and / or styrene are preferred, and copolymer of α-methylstyrene and styrene is more preferred. From the viewpoint of wet grip performance of the rubber composition, the resin content is preferably 1 part by mass or more, more preferably 3 parts by mass or more, per 100 parts by mass of the rubber component, and from the viewpoint of fuel economy, the resin content is preferably 20 parts by mass or less, more preferably 10 parts by mass or less, per 100 parts by mass of the rubber component containing the random copolymer of this embodiment and other rubber components.

[0050] <Additives> In addition to the above, additives such as antioxidants, wax, stearic acid, and vulcanization accelerators may be blended into the rubber composition. Examples of the antioxidant include, but are not limited to, naphthylamine-based antioxidants such as phenyl-α-naphthylamine; diphenylamine-based antioxidants such as octylated diphenylamine and 4,4'-bis(α,α'-dimethylbenzyl)diphenylamine; N-phenyl-N'-isopropyl-p-phenylenediamine, N-(1,3-dimethylbutyl)-N'-phenyl-p-phenylenediamine, N,N'-di-2-naphthyl-p- Examples of the antioxidant include p-phenylenediamine antioxidants such as phenylenediamine; quinoline antioxidants such as polymers of 2,2,4-trimethyl-1,2-dihydroquinoline; monophenol antioxidants such as 2,6-di-t-butyl-4-methylphenol and styrenated phenol; and bis, tris, and polyphenol antioxidants such as tetrakis-[methylene-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate]methane. These antioxidants may be used alone or in combination of two or more. In particular, p-phenylenediamine antioxidants are preferred, and N-phenyl-N'-isopropyl-p-phenylenediamine is more preferred. The content of the antioxidant is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component including the random copolymer of the present embodiment and other rubber components. Examples of waxes include, but are not limited to, petroleum waxes such as paraffin wax and microcrystalline wax; natural waxes such as vegetable wax and animal wax; and synthetic waxes such as polymers of ethylene, propylene, etc. These may be used alone or in combination of two or more. In particular, petroleum wax is preferred, and paraffin wax is more preferred. The wax content is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component including the random copolymer of the present embodiment and other rubber components. As the stearic acid, a conventionally known one can be used, for example, products of NOF Corporation, NOF Corporation, Kao Corporation, Wako Pure Chemical Industries, Ltd., Chiba Fatty Acid Co., Ltd., etc. can be used. These may be used alone or in combination of two or more. The content of stearic acid is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component including the random copolymer of the present embodiment and other rubber components. Examples of the vulcanization accelerator include, but are not limited to, thiazole-based vulcanization accelerators such as 2-mercaptobenzothiazole, dibenzothiazyl disulfide, and N-cyclohexyl-2-benzothiazyl sulfenamide; thiuram-based vulcanization accelerators such as tetramethylthiuram monosulfide and tetramethylthiuram disulfide; sulfenamide-based vulcanization accelerators such as N-cyclohexyl-2-benzothiazole sulfenamide, Nt-butyl-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, N-oxyethylene-2-benzothiazole sulfenamide, and N,N'-diisopropyl-2-benzothiazole sulfenamide; and guanidine-based vulcanization accelerators such as diphenylguanidine, di-orthotolylguanidine, and orthotolylbiguanidine. These may be used alone or in combination of two or more. In particular, sulfenamide vulcanization accelerators are preferred, and N-cyclohexyl-2-benzothiazole sulfenamide is more preferred, because the effects of the present invention can be more suitably obtained. It is also preferred to use a guanidine vulcanization accelerator in combination. The content of the vulcanization accelerator is preferably 0.1 to 5 parts by mass, more preferably 0.2 to 4 parts by mass, based on 100 parts by mass of the rubber component including the random copolymer of the present embodiment and other rubber components.

[0051] <Vulcanizing agents, vulcanization activators, organic peroxides, processing aids, anti-aging agents> In addition to the above-mentioned components, the rubber composition may contain compounding agents conventionally used in the rubber industry, such as vulcanizing agents such as sulfur; vulcanization activators such as zinc oxide; organic peroxides; processing aids such as lubricants; and antioxidants. The vulcanizing agent is not particularly limited, but sulfur can be preferably used. The content of sulfur is preferably 0.5 to 5 parts by mass, more preferably 1 to 3 parts by mass, based on 100 parts by mass of the rubber component including the random copolymer of the present embodiment and other rubber components. This allows the effects of the present invention to be more suitably obtained.

[0052] (Method of manufacturing rubber composition) The rubber composition can be produced by a general method, i.e., by kneading the components in a Banbury mixer, kneader, open roll, or the like, and then vulcanizing the mixture.

[0053] (Use of rubber composition) The rubber composition containing the random copolymer of the present embodiment can be used for each component of a tire (tread, sidewall, carcass, belt, bead, clinch, chafer, etc.), and is particularly suitable for use as a tread. In the case of a two-layer tread, it is composed of a surface layer (cap tread) and an inner layer (base tread). A multi-layered tread can be manufactured by laminating sheets into a predetermined shape, or by feeding the sheets into two or more extruders and forming two or more layers at the head outlet of the extruders.

[0054] <Pneumatic tires> The rubber composition containing the random copolymer of this embodiment is suitable as a raw material for pneumatic tires. Pneumatic tires can be manufactured by a known method using the rubber composition. That is, a rubber component, a plasticizer component, a filler component, and various other additives as necessary are blended, and extruded to match the shape of each tire component such as a tread in the unvulcanized stage, and molded together with other tire components on a tire building machine to form an unvulcanized tire, and the unvulcanized tire is heated and pressurized in a vulcanizer to obtain a pneumatic tire. The pneumatic tire of the present embodiment is suitably used as a passenger car tire, a truck / bus tire, a motorcycle tire, a racing tire, etc., and is particularly suitably used as a passenger car tire. EXAMPLES

[0055] Hereinafter, the present embodiment will be described in more detail with reference to specific examples and comparative examples, but the present embodiment is not limited in any way to the following examples and comparative examples. Various physical properties in the examples and comparative examples were measured by the methods shown below.

[0056] (Random copolymer weight average molecular weight (Mw) and molecular weight distribution) The chromatogram was measured using a GPC measuring device equipped with three columns packed with polystyrene gel, and the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the random copolymer were determined based on a calibration curve using standard polystyrene. The eluent used was tetrahydrofuran (THF) containing 5 mmol / L triethylamine. The columns used were: guard column: Tosoh Corporation (trade name: "TSKguardcolumn SuperH-H"); and columns: Tosoh Corporation (trade names: "TSKgel SuperH5000", "TSKgel SuperH6000", and "TSKgel SuperH7000"). An RI detector (manufactured by Tosoh Corporation under the trade name "HLC8020") was used under conditions of an oven temperature of 40°C and a THF flow rate of 0.6 mL / min. 10 mg of the sample to be measured was dissolved in 20 mL of THF to prepare a measurement solution, and 20 μL of the measurement solution was injected into the GPC measurement device and measured.

[0057] (Confirmation of unimodal molecular weight distribution of random copolymer) The term "monomodal GPC curve" means that when a random copolymer is analyzed by GPC, the slope of the tangent to the elution curve when elution time is changed shows 0° only once. The elution curves of the random copolymers obtained in the production examples described below were differentiated to draw differential elution curves, and the monomodality of the curves was confirmed.

[0058] (Modification rate of random copolymer) The random copolymer was used as a sample for measurement, and the chromatogram was measured by utilizing the adsorption property of the modified basic polymer component on a GPC column packed with silica gel. The measurement sample solution containing the measurement sample and low molecular weight internal standard polystyrene was used to measure the amount of adsorption onto the silica-based column from the difference between the chromatogram measured using the polystyrene-based column and the chromatogram measured using the silica-based column, and the modification rate was calculated. Specifically, it is as follows: Preparation of sample solution for measurement: 10 mg of the measurement sample and 5 mg of standard polystyrene were dissolved in 20 mL of THF (tetrahydrofuran) to prepare a measurement sample solution. GPC measurement conditions using polystyrene columns: Using a Tosoh Corporation product name "HLC-8320GPC," THF was used as the eluent, 10 μL of the measurement sample solution was injected into the device, and a chromatogram was obtained using an RI detector under the conditions of a column oven temperature of 40°C and a THF flow rate of 0.35 mL / min. Three Tosoh Corporation product name "TSKgel SuperMultiporeHZ-H" columns were connected, and a Tosoh Corporation product name "TSKguardcolumn SuperMP(HZ)-H" was connected in front of them as a guard column. GPC measurement conditions using a silica column: Using a Tosoh Corporation product name "HLC-8320GPC", THF was used as the eluent, 50μL of the measurement sample solution was injected into the device, and a chromatogram was obtained using an RI detector under the conditions of a column oven temperature of 40℃ and a THF flow rate of 0.5mL / min. The columns used were "Zorbax PSM-1000S", "PSM-300S", and "PSM-60S", and a guard column "DIOL 4.6×12.5mm 5micron" was connected to the front of the columns. How to calculate the denaturation rate: The total peak area of ​​the chromatogram using the polystyrene-based column was set as 100, the peak area of ​​the sample was set as P1, the peak area of ​​the standard polystyrene was set as P2, the total peak area of ​​the chromatogram using the silica-based column was set as 100, the peak area of ​​the sample was set as P3, and the peak area of ​​the standard polystyrene was set as P4, and the modification rate (mass%) was calculated using the following formula. Modification rate (mass%) = [1-(P2 x P3) / (P1 x P4)] x 100 (In the above formula, P1+P2=P3+P4=100.)

[0059] (Amount of bound styrene in random copolymer) 100 mg of the sample was made into 100 mL of chloroform and dissolved to prepare a measurement sample. The amount of bound styrene (mass%) relative to 100 mass% of the sample random copolymer was measured based on the amount of absorption of ultraviolet light by the phenyl group of styrene (near 254 nm) (measurement device: Shimadzu Corporation spectrophotometer "UV-2450").

[0060] (1,2-vinyl bond content in butadiene part of random copolymer) A measurement sample was prepared by dissolving 50 mg of the random copolymer in 10 mL of carbon disulfide. -1 The absorbance at a predetermined wave number was measured in the range of 100 nm to 150 nm, and the microstructure of the butadiene portion, i.e., the amount of 1,2-vinyl bonds (mol%) was calculated according to the formula of Hampton's method (method described in R.R. Hampton, Analytical Chemistry 21, 923 (1949)) (measuring device: Fourier transform infrared spectrophotometer "FT-IR230" manufactured by JASCO Corporation).

[0061] (Hydrogenation Ratio and Ethylene Structure Amount of Random Copolymer) A large amount of methanol was added to the solution of the random copolymer after the hydrogenation reaction, whereby the conjugated diene polymer before hydrogenation and the hydrogenated conjugated diene polymer were precipitated and recovered. Next, the hydrogenated conjugated diene polymer was extracted with acetone, and the hydrogenated conjugated diene polymer was vacuum dried. 1 The hydrogenation rate and the amount of ethylene structure were measured using the sample for H-NMR measurement. The conditions are as follows: (Measurement conditions) Measuring equipment: JNM-LA400 (JEOL) Solvent: Deuterated chloroform Measurement sample: Samples taken before and after hydrogenation of the polymer Sample concentration: 50mg / mL Observation frequency: 400MHz Chemical shift reference: TMS (tetramethylsilane) Pulse Delay: 2.904 seconds Number of scans: 64 Pulse width: 45° Measurement temperature: 26℃

[0062] (Iodine value of random copolymer) The iodine value of the random copolymer was calculated according to the method described in "JIS K 0070:1992".

[0063] (Glass transition temperature of random copolymer: Tg) The random copolymer was used as a sample, and a DSC curve was recorded in accordance with ISO 22768:2006 using a differential scanning calorimeter "DSC3200S" manufactured by Mac Science, Inc., while heating from -100°C at 20°C / min under a helium flow of 50 mL / min. The peak top (inflection point) of the DSC differential curve was determined as the glass transition temperature.

[0064] (Random copolymer crumb size) <Crumb manufacturing method> The solvent was removed from a polymerization solution of a random copolymer obtained by the method described in the Production Example below by steam stripping to obtain crumbs. The process of obtaining the crumbs is called crumbing. The conditions for climbing are as follows: Water temperature: 90℃ Water amount: 8kg Mixing tank: 30L mixing tank with impeller Agitator blades: 2 turbine blades Agitator rotation speed: 500 rpm Amount of polymer used for cracking: 200g Polymer solution addition rate to the Cramming tank: 30g / min

[0065] <Crumb Median Diameter (D50) Evaluation> The crumbs obtained by crumbing were sieved using a metal mesh sieve (JIS Z 8801-1:2000, manufactured by Okutani Metal Works, Ltd.) to separate them into crumbs corresponding to each mesh size. The opening sizes of the metal mesh sieves used are as follows: 22.4mm, 19mm, 16mm, 13.2mm, 9.5mm, 8mm, 6.7mm, 4mm, 3.35mm, 1.7mm The mass of crumbs caught on each sieve with each mesh size was measured and D50 was calculated.

[0066] [Preparation of hydrogenation catalyst] In the examples and comparative examples described later, the hydrogenation catalyst used in preparing the random copolymer was prepared by the following method. A nitrogen-purged reaction vessel was charged with 1 liter of dried and purified cyclohexane, and 100 mmol of bis(η5-cyclopentadienyl)titanium dichloride was added. With sufficient stirring, an n-hexane solution containing 200 mmol of trimethylaluminum was added, and the mixture was allowed to react at room temperature for approximately 3 days to obtain a hydrogenation catalyst.

[0067] [Production Example 1 (Production of Random Copolymer 1)] Two tank-type pressure vessels having an internal volume of 10 L, an internal height (L) to diameter (D) ratio (L / D) of 4.0, an inlet at the bottom and an outlet at the top, and an agitator as a tank-type reactor and a jacket for temperature control were connected together as polymerization reactors. 1,3-butadiene, from which moisture had been removed in advance, was mixed at 22.0 g / min, styrene at 3.9 g / min, and n-hexane at 175.0 g / min. In a static mixer installed in the middle of the pipe supplying this mixed solution to the inlet of the reactor, n-butyllithium for inactivating remaining impurities was added at 6.0 mg / min, mixed, and then continuously supplied to the bottom of the reactor. Furthermore, 2,2-di(2-tetrahydrofuryl)propane as a polar substance was supplied at a rate of 0.34 mg / min, and n-butyllithium as a polymerization initiator was supplied at a rate of 23.8 mg / min to the bottom of the first reactor, which was being vigorously mixed with an agitator, and the internal temperature of the reactor was maintained at 67°C. The polymer solution was continuously withdrawn from the top of the first reactor and continuously fed to the bottom of the second reactor to continue the reaction at 70°C, and then fed to the static mixer from the top of the second reactor. In the static mixer, 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifying agent at a rate of 24.2 mg / min to modify the growing ends. Next, 10 L of the polymerization solution was transferred to a tank-type pressure vessel equipped with a stirrer and a jacket for temperature control, which was a tank-type reactor having an internal volume of 20 L and an internal height (L) to diameter (D) ratio (L / D) of 4.0, and the internal temperature was adjusted to 80°C, and hydrogen was introduced into the system. Next, a hydrogenation catalyst was added in an amount of 60 ppm (based on titanium) relative to the amount of charged monomer, and the hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. After reaching a predetermined cumulative hydrogen flow rate, the reaction liquid was returned to room temperature and pressure and withdrawn from the reaction vessel to obtain a polymer solution. The obtained polymer solution was crumbed under the above-mentioned crumbing conditions to obtain crumbs of random copolymer 1. The crumbs were separated by particle size using a metal mesh sieve, and the mass fraction at each mesh size was measured to calculate D50. After calculating the D50 of the crumbs, the crumbs were dried for 2 hours in a vacuum dryer heated to 90°C to obtain an analytical sample of random copolymer 1. The polymerization recipe, physical properties and characteristics of the random copolymer 1 are shown in Table 1.

[0068] [Production Example 2 (Production of Random Copolymer 2)] Two tank-type pressure vessels having an internal volume of 10 L, an internal height (L) to diameter (D) ratio (L / D) of 7.0, an inlet at the bottom and an outlet at the top, and an agitator as a tank-type reactor and a jacket for temperature control were connected together as polymerization reactors. 1,3-butadiene, from which moisture had been removed in advance, was mixed at 22.0 g / min, styrene at 3.9 g / min, and n-hexane at 175.0 g / min. In a static mixer installed in the middle of the pipe supplying this mixed solution to the inlet of the reactor, n-butyllithium for inactivating remaining impurities was added at 6.0 mg / min, mixed, and then continuously supplied to the bottom of the reactor. Furthermore, 2,2-di(2-tetrahydrofuryl)propane as a polar substance was supplied at a rate of 0.24 mg / min, and n-butyllithium as a polymerization initiator was supplied at a rate of 19.6 mg / min to the bottom of the first reactor, which was being vigorously mixed with a stirrer, and the internal temperature of the reactor was maintained at 67°C. The polymer solution was continuously withdrawn from the top of the first reactor and continuously fed to the bottom of the second reactor to continue the reaction at 70°C, and then fed to the static mixer from the top of the second reactor. In the static mixer, 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifying agent at a rate of 19.9 mg / min to modify the growing ends. Next, 10 L of the polymerization solution was transferred to a tank-type pressure vessel equipped with a stirrer and a jacket for temperature control, which was a tank-type reactor having an internal volume of 20 L and an internal height (L) to diameter (D) ratio (L / D) of 4.0, and the internal temperature was adjusted to 80°C, and hydrogen was introduced into the system. Next, a hydrogenation catalyst was added in an amount of 60 ppm (based on titanium) relative to the amount of charged monomer, and the hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. After reaching a predetermined cumulative hydrogen flow rate, the reaction liquid was returned to room temperature and pressure and withdrawn from the reaction vessel to obtain a polymer solution. The obtained polymer solution was crumbed under the above-mentioned crumbing conditions to obtain crumbs of random copolymer 1. The crumbs were separated by particle size using a metal mesh sieve, and the weight fraction at each mesh size was measured to calculate D50. After calculating the D50 of the crumbs, the crumbs were dried for 2 hours in a vacuum dryer heated to 90°C to obtain an analytical sample of random copolymer 2. The polymerization recipe, physical properties and characteristics of the random copolymer 2 are shown in Table 1.

[0069] [Production Example 3 (Production of Random Copolymer 3)] Polymerization was carried out in the same manner as for the random copolymer 1 in [Production Example 1] above, except that the addition rate of the polymerization initiator n-butyllithium was changed to 33.5 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane was changed to 0.75 mg / min, and the addition rate of the modifier 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was changed to 34.0 mg / min. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 3 are shown in Table 1.

[0070] [Production Example 4 (Production of Random Copolymer 4)] Polymerization was carried out in the same manner as for the random copolymer 2 in [Production Example 2] above, except that the addition rate of the polymerization initiator n-butyllithium was changed to 27.5 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane was changed to 0.51 mg / min, and the addition rate of the modifier 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was changed to 28.0 mg / min. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 4 are shown in Table 1.

[0071] [Production Example 5 (Production of Random Copolymer 5)] The polymerization conditions were the same as those in the above-mentioned [Production Example 1] except for changing the amount of hydrogen added, and thus a random copolymer 5 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 5 are shown in Table 1.

[0072] [Production Example 6 (Production of Random Copolymer 6)] The polymerization conditions were the same as those in the above-mentioned [Production Example 2] except for changing the amount of hydrogen added, and thus a random copolymer 6 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 6 are shown in Table 2.

[0073] [Production Example 7 (Production of Random Copolymer 7)] Polymerization was carried out in the same manner as for the random copolymer 1 in [Production Example 1] above, except that the addition rate of styrene was changed to 1.3 g / min, the addition rate of butadiene to 25 g / min, the addition rate of the polymerization initiator n-butyllithium to 20.1 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane to 0.26 mg / min, and the addition rate of the modifier 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine to 20.4 mg / min. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 7 are shown in Table 2.

[0074] [Production Example 8 (Production of Random Copolymer 8)] The polymerization conditions other than the amount of hydrogen added were the same as those in the above-mentioned [Production Example 1], and a random copolymer 8 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 8 are shown in Table 2.

[0075] [Production Example 9 (Production of Random Copolymer 9)] The polymerization conditions other than the amount of hydrogen added were the same as those in the above-mentioned [Production Example 2], and a random copolymer 9 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 9 are shown in Table 2.

[0076] [Production Example 10 (Production of Random Copolymer 10)] Polymerization was carried out in the same manner as for the random copolymer 1 in [Production Example 1] above, except that the addition rate of the polymerization initiator n-butyllithium was changed to 39.8 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane was changed to 0.91 mg / min, and the addition rate of the modifier 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was changed to 40.3 mg / min. The polymerization recipe, physical properties and characteristics of the resulting random copolymer 10 are shown in Table 2.

[0077] [Production Example 11 (Production of Random Copolymer 11)] Polymerization was carried out in the same manner as for the random copolymer 1 in [Production Example 1] above, except that the addition rate of the polymerization initiator n-butyllithium was changed to 15.1 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane was changed to 0.14 mg / min, and the addition rate of the modifier 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was changed to 15.3 mg / min. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 11 are shown in Table 3.

[0078] [Production Example 12 (Production of Random Copolymer 12)] The polymerization conditions other than the amount of hydrogen added were the same as those in the above-mentioned [Production Example 1], and a random copolymer 12 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 12 are shown in Table 3.

[0079] [Production Example 13 (Production of Random Copolymer 13)] The polymerization conditions other than the amount of hydrogen added were the same as those in the above-mentioned [Production Example 1], and a random copolymer 13 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 13 are shown in Table 3.

[0080] [Production Example 14 (Production of Random Copolymer 14)] Polymerization was carried out in the same manner as for the random copolymer 1 in [Production Example 1] above, except that the addition rate of the polymerization initiator n-butyllithium was changed to 13.2 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane was changed to 0.11 mg / min, and the addition rate of the modifier 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was changed to 13.4 mg / min. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 14 are shown in Table 3.

[0081] [Production Example 15 (Production of Random Copolymer 15)] Polymerization was carried out in the same manner as in the random copolymer 1 of [Production Example 1] above, except that the addition rate of the polymerization initiator n-butyllithium was changed to 10.2 mg / min, the addition rate of the polar substance 2,2-di(2-tetrahydrofuryl)propane was changed to 0.07 mg / min, and no modifier was added. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 15 are shown in Table 3.

[0082] [Production Example 16 (Production of Random Copolymer 16)] Two tank-type pressure vessels having an internal volume of 10 L, an internal height (L) to diameter (D) ratio (L / D) of 4.0, an inlet at the bottom and an outlet at the top, and an agitator as a tank-type reactor and a jacket for temperature control were connected together as polymerization reactors. 1,3-butadiene, which had been previously dehydrated, was mixed at 22.0 g / min, styrene at 3.9 g / min, and n-hexane at 175.0 g / min. In a static mixer installed in the middle of the pipe supplying this mixed solution to the inlet of the reactor, n-butyllithium for inactivating remaining impurities was added at 6.0 mg / min, mixed, and then continuously supplied to the bottom of the reactor. Furthermore, 2,2-di(2-tetrahydrofuryl)propane as a polar substance was supplied at a rate of 0.34 mg / min, and n-butyllithium as a polymerization initiator was supplied at a rate of 23.8 mg / min to the bottom of the first reactor, which was vigorously mixed with a stirrer, and the temperature inside the reactor was maintained at 67°C. The polymer solution was continuously withdrawn from the top of the first reactor and continuously fed to the bottom of the second reactor to continue the reaction at 70°C, and then fed to the static mixer from the top of the second reactor. In the static mixer, 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifying agent at a rate of 24.2 mg / min to modify the growing ends. The obtained polymerization solution was crumbed under the above-mentioned crumbing conditions to obtain crumbs of random copolymer 16. The crumbs were separated by particle size using a metal mesh sieve, and the weight fraction at each mesh size was measured to calculate D50. After calculating the D50 of the crumbs, the crumbs were dried for 2 hours in a vacuum dryer heated to 90°C to obtain an analytical sample of random copolymer 16. The polymerization recipe, physical properties and characteristics of the random copolymer 16 are shown in Table 4.

[0083] [Production Example 17 (Production of Random Copolymer 17)] Two tank-type pressure vessels having an internal volume of 10 L, an internal height (L) to diameter (D) ratio (L / D) of 3.0, an inlet at the bottom and an outlet at the top, and an agitator as a tank-type reactor and a jacket for temperature control were connected together as polymerization reactors. 1,3-butadiene, which had been previously dehydrated, was mixed at 22.0 g / min, styrene at 3.9 g / min, and n-hexane at 175.0 g / min. In a static mixer installed in the middle of the pipe supplying this mixed solution to the inlet of the reactor, n-butyllithium for inactivating remaining impurities was added at 6.0 mg / min, mixed, and then continuously supplied to the bottom of the reactor. Furthermore, 2,2-di(2-tetrahydrofuryl)propane as a polar substance was supplied at a rate of 0.24 mg / min, and n-butyllithium as a polymerization initiator was supplied at a rate of 25.2 mg / min to the bottom of the first reactor, which was vigorously mixed with a stirrer, and the temperature inside the reactor was maintained at 67°C. The polymer solution was continuously withdrawn from the top of the first reactor and continuously fed to the bottom of the second reactor to continue the reaction at 70°C, and then fed to the static mixer from the top of the second reactor. In the static mixer, 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifying agent at a rate of 25.6 mg / min to modify the growing ends. Next, 10 L of the polymerization solution was transferred to a tank-type pressure vessel equipped with a stirrer and a jacket for temperature control, which was a tank-type reactor having an internal volume of 20 L and an internal height (L) to diameter (D) ratio (L / D) of 4.0, and the internal temperature was adjusted to 80°C, and hydrogen was introduced into the system. Next, a hydrogenation catalyst was added in an amount of 60 ppm (based on titanium) relative to the amount of charged monomer, and the hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. After reaching a predetermined cumulative hydrogen flow rate, the reaction liquid was returned to room temperature and pressure and withdrawn from the reaction vessel to obtain a polymer solution. The obtained polymer solution was crumbed under the above-mentioned crumbing conditions to obtain crumbs of random copolymer 17. The crumbs were separated by particle size using a metal mesh sieve, and the weight fraction at each mesh size was measured to calculate D50. After calculating the D50 of the crumbs, the crumbs were dried for 2 hours in a vacuum dryer heated to 90°C to obtain an analytical sample of random copolymer 17. The polymerization recipe, physical properties and characteristics of the random copolymer 17 are shown in Table 4.

[0084] [Production Example 18 (Production of Random Copolymer 18)] 25,800 g of normal hexane, 3.1 g of the polar substance 2,2-di(2-tetrahydrofuryl)propane, 645 g of styrene, and 2,814 g of 1,3-butadiene were charged into an autoclave reactor having an internal volume of 40 L and an internal height (L) to diameter (D) ratio (L / D) of 4.0. After adjusting the temperature of the reactor contents to 40°C, a cyclohexane solution containing 2.9 g of n-butyllithium was added to initiate polymerization, which was carried out under adiabatic conditions. When the polymerization conversion rate reached 99%, 840 g of butadiene was added and the polymerization was continued for another 5 minutes to obtain a reaction solution containing a polymer. Then, 2.9 g of 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifier and reacted with the active sites of the polymer for 30 minutes. Next, the reaction mixture was heated to 80° C. and hydrogen was introduced into the system. Next, a hydrogenation catalyst was added in an amount of 60 ppm (based on titanium) relative to the amount of charged monomer, and the hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85° C. After reaching a predetermined cumulative hydrogen flow rate, the reaction liquid was returned to room temperature and pressure and withdrawn from the reaction vessel to obtain a polymer solution. The obtained polymerization solution was crumbed under the above-mentioned crumbing conditions to obtain crumbs of random copolymer 18. The crumbs were separated by particle size using a metal mesh sieve, and the weight fraction at each mesh size was measured to calculate D50. After calculating the D50 of the crumbs, the crumbs were dried for 2 hours in a vacuum dryer heated to 90°C to obtain an analytical sample of random copolymer 18. The polymerization recipe, physical properties and characteristics of the random copolymer 18 are shown in Table 5.

[0085] [Production Example 19 (Production of Random Copolymer 19)] The polymerization conditions other than the amount of hydrogen added were the same as those in the above-mentioned [Production Example 17], and a random copolymer 19 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 19 are shown in Table 4.

[0086] [Production Example 20 (Production of Random Copolymer 20)] The polymerization conditions other than the amount of hydrogen added were the same as those in the above-mentioned [Production Example 18], and a random copolymer 20 was obtained. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 20 are shown in Table 5.

[0087] [Production Example 21 (Production of Random Copolymer 21)] A random copolymer 21 was obtained in the same manner as in the above [Production Example 17], except that the modifying agent was changed to N,N-bis(triethoxysilylpropyl)aminopropyl-1-imidazole. The polymerization recipe, physical properties and characteristics of the obtained random copolymer 21 are shown in Table 4.

[0088] [Production Example 22 (Production of Random Copolymer 22)] Two tank-type pressure vessels having an internal volume of 10 L, an internal height (L) to diameter (D) ratio (L / D) of 7.0, an inlet at the bottom and an outlet at the top, and an agitator as a tank-type reactor and a jacket for temperature control were connected together as polymerization reactors. 1,3-butadiene, from which moisture had been removed in advance, was mixed under the conditions of 21.0 g / min, styrene 5.2 g / min, and n-hexane 175.0 g / min. In a static mixer installed in the pipe supplying this mixed solution to the inlet of the reactor, n-butyllithium for inactivating remaining impurities was added at 6.0 mg / min, mixed, and then continuously supplied to the bottom of the reactor. Furthermore, 2,2-di(2-tetrahydrofuryl)propane as a polar substance was supplied at a rate of 1.20 mg / min, and n-butyllithium as a polymerization initiator was supplied at a rate of 23.8 mg / min to the bottom of the first reactor, which was being vigorously mixed with a stirrer, and the internal temperature of the reactor was maintained at 67°C. The polymer solution was continuously withdrawn from the top of the first reactor and continuously fed to the bottom of the second reactor to continue the reaction at 70°C, and then fed to the static mixer from the top of the second reactor. In the static mixer, 2,2-dimethoxy-1-(3-(trimethoxysilyl)propyl)-1,2-azasilolidine was added as a modifying agent at a rate of 24.2 mg / min to modify the growing ends. Next, 10 L of the polymer solution was transferred to a tank-type pressure vessel equipped with a stirrer and a jacket for temperature control, which was a tank-type reactor having an internal volume of 20 L and an internal height (L) to diameter (D) ratio (L / D) of 4.0, and the internal temperature was adjusted to 80°C, and hydrogen was introduced into the system. Next, a hydrogenation catalyst was added at 60 ppm based on titanium with respect to the charged monomer amount, and a hydrogenation reaction was carried out at a hydrogen pressure of 0.8 MPa and an average temperature of 85°C. After reaching a predetermined cumulative hydrogen flow rate, the reaction solution was returned to normal temperature and pressure and withdrawn from the reaction vessel to obtain a polymer solution. The obtained polymer solution was subjected to cramming under the above-described cramming conditions to obtain a cram of the random copolymer 22. The cram was separated by a metal mesh sieve for each particle size, and D50 was calculated by measuring the weight fraction at each mesh opening. After calculating the D50 of the cram, the cram was dried in a vacuum dryer heated to 90°C for 2 hours to obtain an analysis sample of the random copolymer 22. The polymerization formulation, physical properties, and characteristics of the obtained random copolymer 22 are shown in Table 3.

[0089] Using the random copolymers 1 to 15 and 22 of Production Examples 1 to 15 and 22 described above, veils for evaluating the product moisture content (VM) of [Examples 1 to 15 and 16] were produced. Similarly, using the random copolymers 16 to 21 of Production Examples 16 to 21 described above, veils for evaluating the product moisture content (VM) of [Comparative Examples 1 to 6] were produced. The method for producing the VM evaluation veil is shown below. <Production of VM Evaluation Veil> 300 g of the hydrated cram obtained in Production Examples 1 to 22 was used for the production of the VM evaluation veil. The random copolymer cram was dehydrated by passing it through a 6-inch roll heated to 80°C with a clearance of 2 mm 10 times. Subsequently, the dehydrated cram was dried by passing it through a 6-inch roll heated to 110°C 15 times. A rectangular container with dimensions of 42 mm in the long side, 21 mm in the short side, and 40 mm in depth was filled with 35 g of the cram prepared by the above method after heating to 60°C, and compressed with a cylinder at a pressure of 3.5 MPa for 10 seconds to obtain a VM evaluation veil. <Evaluation> Next, as the evaluation of Examples 1 to 16 and Comparative Examples 1 to 6, the dehydration efficiency was evaluated by the product moisture content (VM). The evaluation method of VM is described below. 10 g of the VM evaluation bale was placed in a halogen heater heated to 110°C and heated for 20 minutes. The moisture content (VM) in the sample was calculated from the mass change after heating. The formula for calculating VM is as follows: VM (wt%) = (sample mass before heating - sample mass after heating) / sample mass before heating × 100 From the viewpoint of preventing water from evaporating and causing an increase in pressure in the kneader when a rubber composition using a random copolymer is processed into a tire product, it was determined that a VM of 0.75 wt% or less is satisfactory for practical use. Tables 6 to 9 show the VM in Examples 1 to 16 and Comparative Examples 1 to 6.

[0090] [Table 1]

[0091] [Table 2]

[0092] [Table 3]

[0093] [Table 4]

[0094] [Table 5]

[0095] [Table 6]

[0096] [Table 7]

[0097] [Table 8]

[0098] [Table 9]

[0099] It is clear from Tables 6 to 9 that the veils using the random copolymers of the Examples had improved VM. [Industrial Applicability]

[0100] The random copolymer of the present embodiment has industrial applicability in fields such as tire components, interior and exterior parts of automobiles, anti-vibration rubber, belts, footwear, foams, and various industrial product applications.

Claims

[Claim 1] A method for producing random copolymer crumbs, comprising the steps of: a step of polymerizing a monomer including an aromatic vinyl compound and a conjugated diene compound in a solution to obtain a random copolymer having an aromatic vinyl monomer unit, a conjugated diene monomer unit, and an ethylene structure, and having a unimodal molecular weight distribution measured by GPC of 1.30 to 1.75; Obtaining crumbs by removing the solvent from the solution containing the random polymer; , Obtain crumbs having a median diameter (D50) of 6.0 mm or more and 12.0 mm or less; Method for producing crumbs.

Citation Information

Patent Citations

  • Thermal color printer

    JP1985004081A

  • Recovery of polymer

    JP1989054016A

  • Rubber composition for tire tread

    JP1995238187A

  • Production of rubber-like polymer

    JP1998330404A

  • Modified conjugated diene polymer, modified conjugated diene polymer composition, and rubber composition

    JP2020012101A